Research progress of enhanced recovery after surgery in perioperative nursing of elderly patients undergoing surgery for lung cancer (快速康复外科理念在老年肺癌患者围手术期护理中应用的研究进展) - ZHAO Xin (赵欣); CHEN Congcong (陈聪聪); ZHANG Jiang (张晶) (Association of Integrative Nursing, 2022)
Enhancement of perioperative nursing plays an important role in helping the recovery of elderly patients undergoing surgery for lung cancer. This paper summarized the application of enhanced recovery after surgery (ERAS) in perioperative nursing of elderly patients undergoing surgery for lung cancer, and provided reference for quality improvement of clincal practice. (老年肺癌患者的围手术期护理对促进其术后康复有着重要作用。本文主要总结了快速康复外科(ERAS)理念在老年肺癌患者围手术期护理中的应用进展, 以期为临床进一步完善相关护理提供参考。)